PHYSICOCHEMICAL CHARACTERISTICS OF BUNCH AND OIL COMPOSITION IN A BACKCROSS PROGENY (CAIAUÉ X OIL PALM) X OIL PALM - Ricardo Lopes (Colloquium Agrariae, 2021)
Hybrids between caiaué and oil palm (IEH OxG) are explored in genetic improvement with the main objective of associating the high palm oil productivity of oil palm with resistance of caiaué to Bud Rot (BR) disease. Due to fertility problems, IEH OxG plantations require assisted pollination, which raises the production costs. Backcrossings using oil palm as recurrent parent (BC OGxG) are being evaluated as a solution to restore the fertility of IEH OxG, however, the species contrast to physicochemical characteristics of the bunch and to oil composition, therefore, there is a need to observe how these characteristics vary in BC OGxG. This study evaluated the physicochemical characteristics of the bunch and fatty acid composition of the oil produced by 90 plants from an BC OGxG progeny. A large variation was observed in the progeny, with mean values of 9.0 kg for bunch weight, 46.0% of parthenocarpic fruits in the bunch weight, 72.2% of mesocarp in normal fruit and 86.5% in parthenocarpic fruit, 37.6% of oil in the humid mesocarp of normal fruits and 35.9% in parthenocarpic fruits and 16.4% of oil content in the fresh fruits bunch (OCB). The unsaturated fatty acids C18:1 (52.5%) and C18:2 (10.8%) and the saturated fatty acids C16:0 (30.7%) and C18:0 (4.4 %) stood out in the oil composition. In the progeny BC OGxG is possible to select individuals for high OCB and for a greater or lesser percentage of saturated or unsaturated fatty acids in the oil composition.